A cohort study of vitamins contents in human milk from maternal-infant factors - Qiao, Weicang; Chen, Jingyao; Zhang, Minghui; Wang, Yaling; Yang, Baoyu; Zhao, Junying; Jiang, Tiemin; Chen, Lijun (Frontiers in Nutrition, 2022)
Human milk vitamin content is an important indicator to evaluate the nutritional composition of human milk. This paper investigates the influence of maternal and infant factors on the dynamics of human milk vitamin content. A total of 147 mother-infant pairs from 3 different cities (north-south distribution) in China were selected and 9 major vitamins were measured in 332 human milk samples. The three vitamins (vitamin A, β–carotene, and pantothenic acid) showed significant downward trends with lactation period (| r | > 0.3, p < 0.05). The lactation period factor could explain the negative variation of vitamin A (21.2%) and pantothenic acid (9.5%). The factors of lactation period and oils intake could jointly explain variations of β–carotene (11.8%). (Registration number: NCT02658500).